Cronotopias da memória, da imaginação e do esquecimento: cenas dissensuais em dois filmes de Tata Amaral - Piassi, Vinícius Alexandre Rocha (2019)
This research starts from the void opened by the loss of loved ones during the Brazilian military dictatorship by ex-prisoners and persecuted politicians and relatives of dead and disappeared, to sketch an understanding of the elaboration of authoritarian memory by the art of cinema memory. The discussion about the theme is based on his approach in two productions of contemporary national cinema, the films Hoje (2011) and Trago Comigo (2016), by the São Paulo filmmaker Tata Amaral. In these works, the distance between the dictatorial past and the democratic present is suppressed by the prolongation of the traumas caused by torture and the suffering caused by the disappearance and death of people in the daily lives of those who survived these experiences. In each film, the resurgence of images of the victims in the memory and in the imagination of the survivors and relatives of the dead and disappeared point to the updating of their place in the historical narrative, provoking shakes in the fictional consensus on the dictatorship in Brazil and on the forms of public forgetfulness of the past incited in the Brazilian political culture.